The Use of Educational Games in Programming Assignments: SQL Island as a Case Study - Xinogalos, Stelios; Satratzemi, Maya (Applied sciences, 2022)
Educational games have attracted the interest of instructors and researchers in various fields of knowledge since they seem to motivate students, engage them in the educational process, and improve their performance. Computer programming is, without a doubt, cognitively demanding, and this has resulted in extended utilization of educational games. An important limitation of the relevant research lies in the fact that it is based on volunteer participants, while it is carried out as a side activity in programming courses and not in real-world course settings. In this article, a study investigating the utilization of the educational game SQL Island in the context of an assignment on the Structured Query Language (SQL) in a compulsory undergraduate course on Web programming is presented. Fifty-six students attending the course evaluated the player experience and perceived short-term learning through a questionnaire based on the MEEGA+ model for evaluating educational games targeted to computing education. The results both on player experience and perceived short-term learning were rather positive. Students’ performance in the programming tasks of the game was very good, and the overall intervention proved to be effective. Moreover, conclusions were drawn on the constituent features of educational games that can be effectively used in the context of programming assignments.